Optimal Control of Systems Subject to Input-Dependent Hydraulic Delays - Clerget, Charles-Henri; Petit, Nicolas (IEEE transactions on automatic control, 2021)
In this article, we study the optimal control of systems subject to input-varying hydraulic delays, i.e., systems where the delay on the input depends on the past values of the input through a specific integral relation. The calculus of variations of this problem reveals its nondifferentiable nature. Then, a smooth relaxation is proposed to derive an iterative optimization algorithm. A convergence proof is detailed. The practical interest of the algorithm is evidenced on a numerical example.